2021
DOI: 10.1080/21642850.2021.1903327
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among Kosovar university students during the initial phase of outbreak and lockdown of COVID-19 pandemic

Abstract: Background and Purpose: Measures taken to prevent COVID-19 infections, aside from causing disruptions in many facets of our daily life, have impeded education, including the higher education process, as never seen before on a global scale. Recent studies have indicated the potential negative impact of the COVID-19 pandemic on the mental health trajectory of university students. Anxiety and depression can seriously hamper students' quality of life and educational achievement. This study explored anxiety and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 43 publications
(52 reference statements)
0
23
0
1
Order By: Relevance
“…This approach was because the COVID-19 affected virtually every university student [ 13 , 14 , 15 ], and thus, sampling more students for such a study was prudent. Several similar studies have supported the use of a quantitative approach for studies of this nature [ 19 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach was because the COVID-19 affected virtually every university student [ 13 , 14 , 15 ], and thus, sampling more students for such a study was prudent. Several similar studies have supported the use of a quantitative approach for studies of this nature [ 19 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Students’ reported concerns about their academic performance and declined social interaction because of the pandemic have also been established [ 18 ]. Despite numerous studies investigating the impact of COVID-19 on university students’ mental health, economics, social, education, and related stress, anxiety, and depression reactions in several countries [ 16 , 19 , 20 , 21 , 22 , 23 , 24 ], the perception of safety measures and the impact of anxiety on students may vary from one country to another, including subject-specific needs [ 8 ]. Country-specific data suggest that, as of 5 November 2021, Ghana had a total of 130,608 cases with 128,131 recoveries, 37 severe, 12 critical, 1203 deaths, and 1274 active cases per 100,000 population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of these initial reactions opened several studies on students’ psychological stress and distress. One example was the study by Arënliu and Bërxulli (2020) , who measured the psychological pain of students at the University of Pristina in the early days of the Covidien-19 pandemic in Kosovo. These authors found significant differences among students in their motivation to attend online lessons and their levels of psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Students reported that they were not motivated to participate in online teaching and showed high (moderate to severe) levels of psychological distress, in contrast to students who reported being highly motivated to attend online lessons. It should be kept in mind that these results may have changed in later stages of physical distancing ( Arënliu and Bërxulli, 2020 ) and that there may be an increase in stress levels with prolonged social isolation or quarantine ( Brooks et al, 2020 to Arënliu and Bërxulli, 2020 ). Within this line of studies on students’ experiences, one of the most relevant to the breadth of the sample is the one that has focused on how the pandemic has affected students’ wellbeing and lives ( Van de Velde et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%